2019
DOI: 10.1186/s12905-019-0868-1
|View full text |Cite
|
Sign up to set email alerts
|

A full Brazilian or all natural: understanding the influences on young women’s decision to remove their pubic hair

Abstract: BackgroundResearch indicates that young women are being exposed to increasing pressures to remove pubic hair from their bodies, which has the potential for both negative physical and psychological consequences. Women’s personal choice and reasoning for partaking in pubic hair removal is influenced by broader social influences; however, there is little theory-based research drawing from established decision-making models investigating the underlying processes that lead young women to engage in pubic hair remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
0
9
0
4
Order By: Relevance
“…Pubic hair grooming, defined as partial or full removal of pubic hair, is reported as a common practice among men and women in many countries. [1][2][3][4][5][6][7][8][9][10][11][12] The prevalence of grooming is higher in women compared to men, 9,12 and in younger age groups of both women and men. 3,4,6,9 Several studies report grooming prevalence as greater than 80% among women.…”
Section: Introductionmentioning
confidence: 99%
“…Pubic hair grooming, defined as partial or full removal of pubic hair, is reported as a common practice among men and women in many countries. [1][2][3][4][5][6][7][8][9][10][11][12] The prevalence of grooming is higher in women compared to men, 9,12 and in younger age groups of both women and men. 3,4,6,9 Several studies report grooming prevalence as greater than 80% among women.…”
Section: Introductionmentioning
confidence: 99%
“…Bei 23 453 Teilnehmern ist die mit Abstand am häufigsten praktizierte Methode, unabhängig von nationalen Besonderheiten, die Rasur (Abbildung 2b). 7,9,11,[13][14][15][16]18,19,23,37,43,44,47,48,56,63 Lediglich in Kanada, Brasilien und Italien (54 442 Teilnehmern) werden Waxing-Methoden, insbesondere mit Heißwachs (44%, n = 23 898), häufig und damit gleichhäufig wie die Rasur (42%, n = 23 053) beschrieben. 4,[12][13][14]16,19,23,24,30,34,39,45,48,51,60,61 A B B I L D U N G 2 Prozentualer Anteil beziehungsweise Häufigkeit von (a) Subpopulationen und (b) verwendete Methoden und Verfahren zur Intimhaarentfernung.…”
Section: Epi-und Depilationsmethodenunclassified
“…4,[12][13][14]16,19,23,24,30,34,39,45,48,51,60,61 A B B I L D U N G 2 Prozentualer Anteil beziehungsweise Häufigkeit von (a) Subpopulationen und (b) verwendete Methoden und Verfahren zur Intimhaarentfernung. 7,9,1,[13][14][15][16]18,19,23,37,43,44,47,48,56,63…”
Section: Epi-und Depilationsmethodenunclassified
“…Despite critiques (Sniehotta et al, 2014) and subsequent responses (e.g. Conner, 2015) about the model's utility, the Theory of Planned Behaviour has been established as effective in predicting behaviour in a range of health domains including dietary patterns (McDermott et al, 2015) and alcohol consumption (Cooke et al, 2016) and has been applied to hair removal by women (Obst et al, 2019) but has yet to be applied to male grooming practices. Obst et al (2019) found attitude and perceived behavioural control were significant predictors of young women's intention to remove their pubic hair and intention predicted behaviour, providing support for the applicability of this model to the current health behaviour.…”
Section: Health Behaviour Prediction Modelsmentioning
confidence: 99%
“…According to the Prototype Willingness Model, individuals judge how similar they feel to a prototype (prototype similarity) and how favourable their view of that prototype is (prototype favourability) which both influence the individual’s willingness to perform a behaviour (Gibbons and Gerrard, 1995; Todd et al, 2016). In their study of women’s pubic hair removal, Obst et al (2019) found prototype similarity predicted hair removal intentions after the effects of the TPB constructs had been taken into account. Incorporation of prototype images may account for the potential role of social pressure in the context of male body hair removal.…”
Section: Health Behaviour Prediction Modelsmentioning
confidence: 99%